SURVIVAL CAPACITY OF Arcobacter butzleri INOCULATED IN POULTRY MEAT AT TWO DIFFERENT REFRIGERATION TEMPERATURES - BADILLA-RAMÍREZ, Yanán; FALLAS-PADILLA, Karolina L.; FERNÁNDEZ-JARAMILLO, Heriberto; ARIAS-ECHANDI, María Laura (Revista do Instituto de Medicina Tropical de São Paulo, 2016)
Arcobacter spp. are emerging enteropathogens and potential zoonotic agents that can be transmitted by food and water, being considered a public health risk. The high isolation rate of these bacteria from poultry products suggests that it may be a major source of human infections. One hallmark for differentiating the genus Arcobacter fromCampylobacter includes their growing capacity at low temperatures (15-30 °C) under aerobic conditions. However, little is known about the population density variation of these bacteria at different refrigeration temperatures. The aim of this study was to determine the survival behavior of two different Arcobacter butzleri concentrations (104 CFU/mL and 107 CFU/mL) inoculated on chicken legs and held at two different refrigeration temperatures (4 and 10 °C) throughout storage time. Results have shown that A. butzleri had growing capacity both at 4 and 10 °C. No statistical difference between the survival trends was found for both bacterial concentrations and temperatures tested. This study shows that A. butzleri is a robust species with regard to storage temperature, and represents a potential health risk for poultry meat consumers.